Relationship between socio-descriptive characteristics, burnout syndrome, and quality of life of employees - Rancic, Natasa K.; Veljkovic, Dejan R.; Mirkovic, Momcilo R.; Kulic, Ljiljana M.; Jovanovic, Verica S.; Stamenkovic, Bojana N.; Maksimovic, Natasa S.; Ciric, Vojislav M.; Marinkov-Zivkovic, Emilija M.; Giljaca, Sonja D.; Đorđevic, Gordana; Đorđevic, Ognjen G.; et al. (Frontiers in Public Health, 2024)
Introduction Burnout syndrome develops as a consequence of chronic stress among employees. The study objective was to examine what socio-descriptive characteristics of employees might be associated with the appearance of the occupational burnout and to evaluate the relationship between job burnout and the quality of life among security employees of the professional private security sector in Central Serbia. Methods A multicenter cross-sectional questionnaire-based study was performed. A multivariate logistic regression analysis and ANOVA post choc test was applied. Results A total of 353 respondents (330 male and 23 female) participated in the study. Female sex and older age were associated with a higher risk of total burnout and the development of emotional exhaustion while male sex, higher education, and managerial position were associated with higher personal achievement and lower risk of total burnout. Male sex, marital union, two or more children, and direct contact with clients were significantly associated with a lower quality of life of employees. A significant negative correlation was found between total burnout and the Physical Health Composite Score (PHC) score with a correlation coefficient (rs) of −0.265 (95%CI from −0.361 to −0.163); between total burnout and the and Mental Health Composite Score (MHC) score with a rs of −0.391 (95%CI from −0.480 to −0.301); and between total burnout and TQL score with a rs of −0.351 (95%CI from −0.445 to −0.258). Conclusion Female sex and older age were associated with a higher risk of total burnout and the development of EE while a managerial position and higher education were protective factors in relation to the development of burnout. Male sex, marital union, two or more children, and direct contact with clients were significantly associated with a lower quality of life of the employees. Shift work significantly reduced the total quality of life, while managerial positions increased the quality of life.